MATURE CYSTIC TERATOMA WITH PAPILLARY THYROID CARCINOMA IN A PATIENT WITH THYROID NODULES - Lusica, Patricia Marie; Jimeno, Cecilia; Toral, Jean Anne (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE We present a 37-year-old Filipino female who was apparently well and has never been hospitalized. She underwent an annual wellness medical exam where an incidental finding of an ovarian new growth on the left was found. Laparoscopic surgery was done and histopathology revealed mature cystic teratoma with papillary thyroid carcinoma, composed of thyroid follicle with a 0.2 cm area. Thyroid work-up showed normal thyroid function tests, and ultrasound described nodules on the left lobe, the largest measuring 1.7 x 1.3 x 1.0cm, TIRADS 3. Fine needle aspiration biopsy was done showing colloid goiter with cystic change. This highlights the management issue arising from a rare case of papillary thyroid carcinoma in an ovarian teratoma in a patient with thyroid nodules. Treatment options range from aggressive measures including bilateral salpingo-oophorectomy and total thyroidectomy with subsequent radioactive iodine therapy, to surgical removal of the teratoma with serial monitoring of the thyroid with ultrasonography.